2012
DOI: 10.1007/s00228-012-1213-x
|View full text |Cite
|
Sign up to set email alerts
|

The adverse event profile of pregabalin across different disorders: a meta-analysis

Abstract: Although drug-resistant partial epilepsy is associated with a higher probability of developing vestibulo-cerebellar AEs, the risk for PGB toxicity does not differ across distinct disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 39 publications
0
28
0
Order By: Relevance
“…Recent evidence, however, suggests that non-epilepsy studies can be merged with epilepsy studies in meta-analyses of RCTs of AEDs [36,50,54,55]. Thus, by taking into account the little drug interaction of LEV [27] we decided to extend the target group also to non-epileptic patients.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Recent evidence, however, suggests that non-epilepsy studies can be merged with epilepsy studies in meta-analyses of RCTs of AEDs [36,50,54,55]. Thus, by taking into account the little drug interaction of LEV [27] we decided to extend the target group also to non-epileptic patients.…”
Section: Discussionmentioning
confidence: 96%
“…Only long-term observational studies provided data about an increased risk of psychiatric disorders in a subset of patients with pre-existing mood disorders [20], likely due to a genetic predisposition [44]. These AEs are infrequent with several AEDs but significantly associated with PER [54]. Dizziness, which is a subjective AE, was the only AE related to vestibulocerebellar/brainstem dysfunction associated with LEV.…”
Section: A N U S C R I P Tmentioning
confidence: 92%
“…These mutations are all recessive, with the heterozygotes showing no significant behavioral effects (Barclay et al, 2001). Interestingly, ataxia is one of the adverse events reported when gabapentin and pregabalin are used therapeutically (Beal et al, 2012;Zaccara et al, 2012).…”
Section: A a 2 D Subunit Genes And Gene Productsmentioning
confidence: 99%
“…For example, in some RCTs in which patients were recruited with more severe epilepsies and treated with high doses of AEDs, more AEs might actually affect all groups of patients regardless the treatment administrated. Recent meta-analyses aimed at assessing tolerability profile of pregabalin [19] and lacosamide [20] across different disorders, have shown that patients treated with placebo display significantly different percentages of AEs with higher percentages in epilepsy patients with respect to patients with other diseases. This is not surprising as epilepsy patients recruited in placebo-controlled studies are drugresistant and treated with high doses of several AEDs.…”
Section: Discussionmentioning
confidence: 99%